Productive Zakat Empowerment Analysis In BAZNAS Institutions - Ramadhan, Muhamad Arya; Permana, Deden Diki; Gumilar, Rahmat (Journal of Islamic Economic Scholar, 2023)
The problem of this research leads to the distribution of productive zakat funds to mustahiq and human resources who do not yet understand both the community and BAZNAS of Ciamis Regency regarding this zakat. In its distribution, it has not been able to fulfill the objectives of productive zakat.After receiving assistance to the mustahiq. The purpose of channeling zakat funds is to increase the business of mustahiq and hope that these mustahiq will not always be mustahiq but will be able to become muzakki in the future. This type of research is a descriptive qualitative research, with the specification of field research. Descriptive qualitative research is writing that aims to describe the status of phenomena in a systematic and rational manner. Qualitative research methods in practice depend on the ability of the research, in explaining the phenomena studied in a descriptive form. This research was conducted at Baznas Ciamis Regency. The data obtained are from interviews with informants. The results of this study indicate that the distribution of productive zakat funds to increase mustahiq business in Ciamis Regency has not been running effectively, where there are several problems including the problem of human resources at BAZNAS which are few, mustahiq who do not understand the concept from productive zakat and lack of commitment when managing zakat funds, and the absence of a clear system resulting in less precise targeting in determining mustahiq and inaccurate distribution. The solution for solving this problem is where the informants agreed that BAZNAS should provide education and assistance to productive zakat mustahiq so that their businesses can develop, and make guidelines in the management of productive zakat both in determining mustahiq and its distribution